2001
DOI: 10.1161/hc4801.100351
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Time After Gd-DTPA Injection Is Critical in Using Delayed Enhancement to Determine Infarct Size Accurately With Magnetic Resonance Imaging

Abstract: Background-In patients with acute myocardial infarction (MI), delayed enhancement is seen in MRI 5 to 7 minutes after gadolinium-diethylenetriamine pentaacetic acid (Gd-DTPA) injection, and the enhancement occurs in regions that later show recovery of function. However, in a canine model of acute MI, delayed enhancement 20 to 30 minutes after injection only occurs in necrotic regions and not in surrounding, reversibly injured myocardium. The objective of the present study was to determine (1) if the size of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
159
7
4

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(181 citation statements)
references
References 21 publications
11
159
7
4
Order By: Relevance
“…1 We found that 2 days after MI, there exists an area at the periphery of the infarct that has a highly transient T1 value. Within the first 5 to 10 minutes after gadolinium-diethylenetriamine pentaacetic acid (Gd-DTPA) injection, the T1 of this region was similar to infarct, but 20 minutes after contrast injection, its T1 value was similar to normal myocardium.…”
Section: Responsementioning
confidence: 68%
See 2 more Smart Citations
“…1 We found that 2 days after MI, there exists an area at the periphery of the infarct that has a highly transient T1 value. Within the first 5 to 10 minutes after gadolinium-diethylenetriamine pentaacetic acid (Gd-DTPA) injection, the T1 of this region was similar to infarct, but 20 minutes after contrast injection, its T1 value was similar to normal myocardium.…”
Section: Responsementioning
confidence: 68%
“…The changes in size of the hyperenhanced regions observed by Oshinski et al, 1 however, were likely caused by an incorrect implementation of the MRI technique. As we have described previously, the MRI technique requires that the correct inversion time be chosen in order to "null" normal myocardium.…”
Section: To the Editormentioning
confidence: 88%
See 1 more Smart Citation
“…Delayed images have to be acquired between 10 and 30 min post-injection of the contrast media. 43 A too early acquisition will overestimate the size of the myocardial infarct, 44 whereas a too late acquisition will result in poor contrast to noise ratio, due to an excessive wash out of the contrast media. It is important to remember that not only will the time post-injection influence the size of the myocardial infarct, but also the type of MR sequences used.…”
Section: Myocardial Hibernationmentioning
confidence: 99%
“…Most MR protocols utilize a T 1 -weighted inversion-recovery (IR) prepared fast gradient echo (GRE) segmented k-space acquisition with imaging performed 10 -20 minutes after the intravenous administration of an extracellular gadolinium (Gd)-based contrast agent (5). With this approach, the optimal inversion time (TI) is adapted to suppress signal from normal myocardium (6,7), while the infarcted tissue appears hyperintense (bright) because of the delayed uptake and retention of Gd-based contrast media. DE imaging exhibits excellent contrast between infarcted and normal myocardium.…”
mentioning
confidence: 99%